The Role of International Law in Safeguarding Indonesia’s Sovereignty: A Case Study of the North Natuna Sea - ZUBAIDI, Abdul Khakim Mahfud; WIYANA, Rachmat Indra; RAMADHANI, Syafitri Nur (Indonesia Strategic Sustainability, 2024)
Purpose:This study aims to explore and understand the role of international law in reinforcing Indonesia's sovereignty, particularly in resolving the North Natuna Sea territorial dispute, while considering the relevant principles of international law.Methodology:The methodology employed in this research is qualitative descriptive. It aims to provide an in-depth description of the role of international law in safeguarding Indonesia's sovereignty through the analysis of relevant secondary sources and available case studies.Findings:This study demonstrates the vital role of international law in protecting Indonesia's sovereignty, particularly in maritime disputes like those over the North Natuna Sea. It highlights the importance of frameworks like UNCLOS in supporting Indonesia's territorial claims and using international legal instruments for diplomacy and dispute resolution. The research also reveals Indonesia's challenges in enforcing these laws, particularly concerning illegal fishing, while emphasizing the need for stronger domestic enforcement aligned with international standards to safeguard maritime sovereignty.Implication:This research provides valuable insights for academicians, practitioners, and policymakers by deepening their understanding of international law's role in protecting national sovereignty and promoting effective maritime governance. It emphasizes the need for aligning domestic laws with international standards. Additionally, the study reminds fishermen and maritime professionals to exercise caution when crossing territorial waters, highlighting the risks of non-compliance and legal consequences.